Pengaruh Pendekatan Realistic Mathematic Education (RME) Terhadap Kemampuan Pemahaman Konsep Matematis Siswa - Windy Putri Maslita Sitanggang; Asmin Asmin (Lembaga Pengembangan Kinerja Dosen, 2023)
This study aims to determine the effect of the Realistic Mathematical Education (RME) approach on the ability to understand mathematical concepts in class VIII students of SMP IT Al-Hijrah 2 Deli Serdang Private Middle School in the 2022/2023 academic year. The type of research used is Quasi Experimental with a Pretest-Posttest Control Group Design. The sample used was 35 students who were selected through a purposive sampling technique. Data collection techniques are carried out using test instruments. Data analysis technique is done by descriptive analysis. The results of the descriptive analysis show that the average value in the experimental class is 87.3935 and in the control class is 54.3639, which means that there is a difference in the posttest average scores in the experimental class and the control class. Based on the Independent Sample T-Test, the value of Sig. (2-tailed) of 0.000 < 0.05. The tcount value is 8.428 and the ttable value is 2.03452, which means that tcount > ttable then H0 is rejected and Ha is accepted. From the results of this study, it can be concluded that there is an influence of the Realistic Mathematical Education (RME) approach on the ability to understand mathematical concepts in class VIII students of Private Middle School IT Al-Hijrah 2 Deli Serdang.